Follow-up of Chrysomya bezziana Myiasis in a buffalo heifer with notes on larval microscopy, morphology, and taxonomy (Zoo Botanica, 2025)
This study documents a case of wound myiasis, providing detailed taxonomic and light micrographic data on the causative pest species. The findings highlight critical gaps in livestock healthcare management in rural Khyber Pakhtunkhwa, Pakistan, where farmers often rely on unqualified veterinary practitioners due to limited awareness of proper animal healthcare. In the present case, an unskilled technician administered antibiotic therapy for three days without addressing the myiasis, whereas a qualified veterinarian later confirmed the diagnosis and implemented appropriate treatment. Traditional remedies remain prevalent in the management of animal ailments. Here, a crude 1:1 mixture of Seguvan® (Trichlorfon 98% w/w, Symans Pharmaceuticals, Lahore, Pakistan) and phenolphthalein was applied to eliminate maggots, resulting in rapid expulsion of superficial larvae. However, deeper larvae required mechanical extraction post-mortem. Following maggot removal and necrotic tissue debridement, accelerated wound healing and behavioral recovery were observed. For larval identification, Puri’s (gum-chloral) mounting medium proved optimal in clearing morphological features. Key diagnostic characters, including the cephalo-pharyngeal skeleton, intersegmental spines, and anterior and posterior spiracles, were instrumental in confirming  Chrysomya bezziana as the causative agent. This case underscores the need for improved veterinary care and farmer education to enhance livestock health outcomes in resource-limited settings
Keywords: Chrysomya bezziana; myiasis; buffalo; larvae; taxonomy; cephalopharyngeal skeleton